#TITLE_ALTERNATIVE# - WIDYANANDA WINARDHI (NIM : 10212076), CHANDRA
The physical quantities of reservoir rocks like porosity, permeabilit, capillary pressure, conductivity, and so forth are very usefull in determining the quality of a reservoir. Usually, measurements were carried out in the lab and takes quite a long time and can damage the reservoir rock sample. Digital Rock Physics (DRP) was developed as the solution of the problem which uses digital images of rock to get physical quantities necessary to determine the quality of the reservoir. Digital Rock Physics (DRP) is a digital-based method where the rock sample is converted into digital images using CT-Scan. This image is then processed to obtain the desired physical quantity. In this study, Bruker SkyScan 1173 𝜇CT-Scan is used. There are seven mode with different resolutions that are developed in this study. Physical quantities such as porosiy, specific surface area, and permeability then will be calculated from all digital images from all of the mode and will be compared with the physical quantities from lab measurement, it will also be compared between each other of the mode to get the best scanning mode. The result show similiarity for porosity digital analysis and porosity from the laboratory measurement. The porosity per slice result shows that sample A is more homogen than sample B which is more heterogen. The permeability result show differences between the simulation and the laboratory measurement.